Kontribusi Pembelajaran Akhlak Dalam Mengatasi Perilaku Delinkuen Pada Santri di Pondok Pesantren Bale Dakwah An Nabawi Kabupaten Lombok Timur Nusa Tenggara Barat - Iswandi, Taufan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Education is something that is very important and should not be ignored in human life, while character is a trait that is firmly embedded in a person then transforms into an action without requiring protracted consideration and thought. If the action is good then it is called praiseworthy morals, and if the action is bad then it is called despicable morals. Moral education and planting morals in every lesson will help in socializing with the environment, both in the family, school and society. So that later it will be accustomed to behavior that reflects religious values. The planting of moral values and material must also be accompanied by planting the benefits and uses of children in moral behavior, so that children understand and understand what they do and say. The application and development of learning and moral education at Bale Dakwah An Nabawy Islamic Boarding School in the process of improving quality underlies its education with noble morals in order to achieve education whose results are satisfactory not only in theory but also in practice in everyday life in the community.